Enzyme‐Responsive Polymer Nanoparticles via Ring‐Opening Metathesis Polymerization‐Induced Self‐Assembly. Issue 2 (3rd September 2018) - Wright, Daniel B.; Thompson, Matthew P.; Touve, Mollie A.; Carlini, Andrea S.; Gianneschi, Nathan C.
Abstract: Open‐to‐air aqueous‐phase ring‐opening metathesis polymerization‐induced self‐assembly (ROMPISA) is reported for forming well‐defined peptide polymer nanoparticles at room temperature and with high solids concentrations (10 w/w%). For these materials, ROMPISA is shown to provide control over molecular weight with high conversion while open‐to‐air. Moreover, these peptide polymer nanoparticles can spontaneously rearrange into larger aggregate scaffolds in the presence of the proteolytic enzyme, thermolysin. This work demonstrates the robust nature of ROMPISA, highlighted here for the preparation of stimuli‐responsive nanostructures in one pot, in air. Abstract : Peptide‐functionalized polymer nanoparticles, both spherical micelles and framboidal vesicles, are formed via ring‐opening metathesis polymerization‐induced self‐assembly. When incubated with protease, the peptides are cleaved and the particles undergo an in situ reorganization into large macromolecular aggregates.